2006
DOI: 10.1002/cbic.200600188
|View full text |Cite
|
Sign up to set email alerts
|

The Reaction of Hydrogen Atoms with Methionine Residues: A Model of Reductive Radical Stress Causing Tandem Protein–Lipid Damage

Abstract: The occurrence of tandem damage, due to reductive radical stress involving proteins and lipids, is shown by using a biomimetic model. It is made of unsaturated lipid vesicle suspensions in phosphate buffer in the presence of methionine, either as a single amino acid or as part of a protein such as RNase A, which contains four methionine residues. The radical process starts with the formation of H(.) atoms by reaction of solvated electrons with dihydrogen phosphate anions, which selectively attack the thioether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

6
2

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 47 publications
4
53
0
Order By: Relevance
“…On the contrary, H • atoms probably attack the enzyme at a more restricted number of sites, perhaps away from the surface and also the far-reaching Tyr can be damaged. A confirm of this behaviour is given by the absence of aggregate formation after H • atom attack [5] , whereas highly aggregated forms of the enzyme have been found under oxidative stress conditions [6,10], since the TyrO • radicals give rise easier to inter-molecular reactions than intra-molecular ones. Since three Tyr "buried" can be probably identified with Tyr-25, -92 and -97, the initial H • radical attack should take place on one or two of them.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…On the contrary, H • atoms probably attack the enzyme at a more restricted number of sites, perhaps away from the surface and also the far-reaching Tyr can be damaged. A confirm of this behaviour is given by the absence of aggregate formation after H • atom attack [5] , whereas highly aggregated forms of the enzyme have been found under oxidative stress conditions [6,10], since the TyrO • radicals give rise easier to inter-molecular reactions than intra-molecular ones. Since three Tyr "buried" can be probably identified with Tyr-25, -92 and -97, the initial H • radical attack should take place on one or two of them.…”
Section: Resultsmentioning
confidence: 88%
“…In fact, the H • -induced desulfurisation involving these residues yield α-aminobutyrric acid (Abu) and Ala (reactions (5) and (6)). In addition, the reductive radical attack towards Met residues has been recently found to yield diffusible sulfur radicals able inducing damages in cellular membranes [4][5][6]. ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This first detection is then associated to proteomic analyses, and this approach is expected to open the way to molecular libraries useful for detecting damages in biological samples. We studied bovine pancreatic RNase A individuating both methionine and cystine reactive sites, with modification of Met and Cys to -amino butyric acid (Aba) and alanine (Ala) residues, respectively (Ferreri et al, 2006b;Ferreri et al, 2008). The sequence of amyloid -peptide of 40 amino acids, where only the Met residue is present as a S-containing amino acid, was also studied for its connections with the alteration reported in the Alzheimer disease.…”
Section: Radical-based Modifications For Protein Librariesmentioning
confidence: 99%
“…We showed that the reaction of H atoms with peptides/proteins determines Met conversion into the non-genetically coded amino acid a-aminobutyric acid (Aba). We have identified this chemical mutation in Met-enkephalin [25], b-amyloid [26], bovine RNase A [27,28], human serum albumin [29], and various metalloproteins [30]. This reactivity has also been placed in a biomimetic context, since it has been suggested as molecular basis of the tandem protein-lipid damage [23,24].…”
Section: Introductionmentioning
confidence: 99%